?SYNTHESIS AND BIOLOGICAL ACTIVITY OF 1-(4-METHYL-2-0XO-2H-I-BENZOJlYRAN- 7-YLOXOACETYL)-4-ALKYLTHIOSEMICARBAZIDES; 1,3,4-THIADIAZOLES AND 1,2,4-TRIAZOLES. - ELTAMANY, S.H.; DEEN, I.M. EL-; FATTAII, M.E.ABDEI.- (Biological Sciences - PJSIR, 1995)
A series of 1-(4-methyl-2-o"o-211-I-benzopyran-7-ylo:)-4-alkylthiosemicarbazides. S-triazoand their methyl derivatives has been synthesized by condensation of 4-methyl-2-oxo-211-I-bellzopyran-7-ylo"o-acctyl hydra- zinc with alkyl isothiocyauatcs. Subcqucnt ring closure of the substituted thioscmicarbazidcs yielded the S-trial.Olcs. and reaction with methyl iodide gave the corresponding methyl derivatives. The substituted I.J.4-thiadiazolcs have been synthesized by cyclodchydration of the substituted thioscmicarhazidcs with phosphoric acid. The biological activity of some new compounds is reported.